Inducing chemical reactivity on specific sites of a molecule using the Coulomb interaction exerted by a low energy electron. Issue 9 (26th January 2018) - Davis, Daly; Sajeev, Y.
Abstract : Site-specificity in the resonant attachment of low energy electrons to molecular targets is used for engineering chemical reactivity. Abstract : Remarkable site-specificity in the resonant attachment of low energy electrons (LEEs) to molecular targets is proposed as an efficient method for inducing chemical reactivity on specific sites of molecules. The Coulomb interaction between the attached electron and the most polarizable molecular electrons localized on the attached site is the reason for site-specific chemical reactivity. The Coulombically induced site-specific chemical reactivity is best illustrated by the LEE induced chemical transformation of a weakly bound molecular complex into a strong covalent adduct. The chemical transformation occurs due to the Coulombically induced nucleophilicity on a specific molecular moiety in the complex. A simple strategy for inducing site-specific chemical reactivity using a LEE may find new avenues in chemical synthesis.